Does the High or Low of Corporate Social Responsibility Disclosure Affect Tax Avoidance? - Firda Ayu Amalia; Eny Suprapti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Research aims: This research aimed to empirically prove the difference of the extent of Corporate Social Responsibility (CSR) disclosure towards tax avoidance.Design/Methodology/Approach: 38 companies listed in Indonesia Stock Exchange (IDX) in 2017 were selected through purposive sampling. The analysis methods used were the independent t-test and the SPSS version 24.Research findings: The results showed that there was no difference between the companies with high CSR disclosures and those with the low ones towards tax avoidance. This indicates that despite the high and low disclosures, the companies’ CSR disclosures generate the same impact towards tax avoidance.Theoretical contribution/ Originality: This research has a novelty in the form of a comparison of CSR disclosures by companies and their impact on tax avoidance.Practitioner/Policy implication: Furthermore, the practical contribution to the government, especially the Directorate General of Taxes, is that CSR disclosure is used by companies to gain legitimacy from the public, especially investors. CSR disclosure is not for window dressing to avoid tax.Research limitation/Implication: The limitation in this study is the number of samples is less representative in representing the population. This is due to the small number of companies listed on the IDX in reporting and disclosing CSR in the sustainability report.